Survey of Physical Fitness Training Programs to Improve VO2max among Automotive Department Students - Khusna, Habwa Isna Malikatul; Manullang, Jujur Gunawan; Handayani, Widya (Yayasan Sembilan Pemuda Indonesia, 2023)
The purpose of this research is (1) to determine the time period for implementing a physical fitness training program to improve the VO2Max of Automotive Department students, (2) to identify the fitness training program given to Automotive Department students to improve their VO2Max, (3) to understand the process of implementing physical fitness training programs that can increase the VO2Max of Automotive Department students, and (4) to determine whether there is an improvement in the VO2Max results of Automotive Department students after being given a physical fitness training program created by the Physical Education teacher. This research uses a qualitative descriptive design. The research is conducted in three vocational schools in the Empat Lawang regency, namely SMK N 1 Empat Lawang located in the Tebing Tinggi district, SMK N 2 Empat Lawang located in the Pendopo district, and SMK N 3 Empat Lawang located in the Paiker district. Data collection procedures include direct interviews with the Physical Education teacher, direct observations of SMK N 1 Empat Lawang, SMK N 2 Empat Lawang, and SMK N 3 Empat Lawang, and documentation to obtain relevant data. The survey findings and results obtained from interviews, observations, and documentation to obtain data can be summarized as follows: The fitness training program created by the Physical Education teachers for a semester or six months, involves running activities in all three vocational schools, while SMKN 1 Empat Lawang also includes push-ups and sit-ups activities. The fitness training program is conducted once a week during the Physical Education class. The results show that after the implementation of the fitness training program, there is an improvement in the VO2Max of Automotive Department students.